Brainfluence : 100 ways to persuade and convince customers with neuromarketing - Dooley, Roger, 1952- (Wiley, 2012)
"Neuromarketing studies the way the brain responds to various cognitive and sensory marketing stimuli. Analysts use this to measure a consumer's preference, what a customer reacts to, and why consumers make certain decisions. This scientific approach to marketing has helped many brands and companies determine how to best market their products to different demographics and consumer groups. Brainfluence explains how to practically apply neuroscience and behavior research to everyday marketing problems. This book is designed to be a practical guide with quick and easy takeaways offered in 60 short chapters, each containing one key strategy. The chapters are organized into major groups, mainly by application: in-person sales, Web marketing, print advertising, and many others. The book explains several key concepts, including: New insights into what makes people buy, Ways for brands to form emotional bonds with customers, Short, easy to digest ideas that can be accessed in any order, Techniques for all types of businesses, including small businesses and non-profits This book contains practical, easy-to-understand ways to improve marketing, advertising, and sales efforts"--Resumé vydavatele
Keywords: neuromarketing; marketing -- psychologické aspekty; psychologie reklamy; spotřebitelé; spotřebitelské chování; marketing -- psychological aspects; psychology of advertising; consumers; consumer behavior; příručky; handbooks and manuals